2014
DOI: 10.1002/jobm.201300805
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heavy metals on growth response and antioxidant defense protection in Bacillus cereus

Abstract: Bacterial cells in aerobic environment generate reactive oxygen species which may lead to oxidative stress, induced by a wide range of environmental factors including heavy metals. In the present context an attempt has been made to determine the toxic impact of cadmium and copper on growth performance, oxidative stress, and relative level of antioxidant protection in Bacillus cereus. Outcome of this study suggests that both the metal ions depleted the growth rate in this organism with respect to time and conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 58 publications
(61 reference statements)
2
10
0
1
Order By: Relevance
“…c,d) indicated the presence of two major bands around 200 and 180 kDa in the presence of metal. The activity of catalase was found to increase when chromium concentration increased from 300 to 2000 mg l −1 (Table ) which correlates with the previous findings on copper‐resistant B. cereus (Behera et al ). Two white bands in purple background around 60–90 kDa in gel assay indicated GPX activity (Fig.…”
Section: Resultssupporting
confidence: 90%
“…c,d) indicated the presence of two major bands around 200 and 180 kDa in the presence of metal. The activity of catalase was found to increase when chromium concentration increased from 300 to 2000 mg l −1 (Table ) which correlates with the previous findings on copper‐resistant B. cereus (Behera et al ). Two white bands in purple background around 60–90 kDa in gel assay indicated GPX activity (Fig.…”
Section: Resultssupporting
confidence: 90%
“…37 Additionally, exposure to high levels of copper have been shown to interfere with the activity of manganese-dependent SodA. 38 We found that deletion of sodA in either the TIGR4 or the Δ copA background did not significantly alter sensitivity to copper stress. (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Respecto a las bacterias, Cidre et al 2017 portado algunas cepas del género Serratia y Bacillus con alto nivel de resistencia a cobre, habiendo encontrado la presencia de genes pertenecientes al cluster pco multicobre oxidasa y al cluster sil involucrado en la resistencia a Cu y Ag en especies del género Serratia y otras gram negativas. Del mismo modo, Behera et al (2014) en el estudio de respuesta antioxidativa de B. cereus frente a cadmio y cobre, encontraron que ambos metales inducían diferentes respuestas, donde la respuesta frente al cobre estaría relacionada con la producción de catalasas. Así mismo, algunas cepas de B. cereus mostraron alta capacidad de biosorción de cobre (Rohini & Jayalakshme 2015, Oladipo et al 2018b, encontrándose la presencia de genes de resistencia al cobre en el cromosoma y que el grado de biosorción era dependiente a las condiciones del medio cultivo y entorno (Rohini & Jayalakshme 2015).…”
Section: Resultados Y Discusiónunclassified